PENETAPAN INDEKS HARGA SAHAM LQ45 DENGAN PERTIMBANGAN TINGKAT INFLASI DAN TINGKAT SUKU BUNGA SERTIFIKAT BANK INDONESIA (SBI) PADA BURSA EFEK INDONESIA (BEI) - Linna Ismawati; Jatnika Dwi Asri; Widya Irmanisaa Yuliastuti (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2025)
The Study phenomenon aimed to find out the influence of rate of Inflation, rate of Interest of SBI toward LQ45 whether in partial or simultaneously at Indonesian Stock Exchange in 2018-2023 periods. The design analysis used is Multiple regression analysis, classical assumption test, correlation analysis of Pearson, determination coeficient, and hypothetical testing using T test dan F test. The result shows that variable the rate of Inflation partially has found there is an negative significant influence toward LQ45, and rate of interest of SBI had a partially significant influence toward LQ45. Simultaneously rate of Inflation and rate of Interest of SBI had a significant influence toward LQ45.